Accelerating urbanization explained: The role of information - Guanghua Wan; Yan Zhang (Asian Development Bank Institute (ADBI), 2017)
In this paper, we argue that urbanization has accelerated in the last few decades, and that this largely overlooked phenomenon cannot be explained by existing empirical models of urbanization. Consequently, we explicitly bring forward the role of information in driving urbanization, focusing on information and communication technology (ICT), especially the Internet. For this purpose, we develop a simple two-sector general equilibrium model, demonstrating the potential effect of information on the urbanization rate. The prediction from the theoretical model is then verified by cross-country regressions based on 1960-2013 data from 109 non-OECD countries. Both fixed effects and IV-fixed effect results show that: (1) information is important in explaining the acceleration of urbanization; (2) the conventional push-pull factors become weak as the urbanization drivers; and (3) the results are robust to different regions, different information proxies, and urbanization quantiles.
Keywords: O18; D8; O15; 330; Information and Communications Technology; Urban development